2014
DOI: 10.1186/s12879-014-0570-8
|View full text |Cite
|
Sign up to set email alerts
|

Dengue NS1 antigen as a marker of severe clinical disease

Abstract: BackgroundEarly detection of complications significantly reduces dengue associated mortality and morbidity. We set out to determine if the NS1 rapid antigen detection test could be used as a point of care test to predict severe disease.Methods186 adult patients with confirmed dengue were enrolled during day 3-8 of illness. Clinical and laboratory parameters were recorded during the course of the illness and NS1 antigen levels were determined using both the Panbio dengue early ELISA (Panbio, Australia) and a NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 31 publications
4
81
2
7
Order By: Relevance
“…Dengue NS1 antigen has been shown previously to associate with DHF, and indeed we found that it could also be considered as a marker of severe clinical disease [10]. In addition, our previous studies showed that serum IL-10 levels were also associated with severe dengue [7,8].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Dengue NS1 antigen has been shown previously to associate with DHF, and indeed we found that it could also be considered as a marker of severe clinical disease [10]. In addition, our previous studies showed that serum IL-10 levels were also associated with severe dengue [7,8].…”
Section: Resultssupporting
confidence: 73%
“…It has also been shown that dengue NS1 protein was associated with severe clinical disease and that a level of > 600 ng/ml in the first 72 h of illness was associated with the development of DHF . We also found that dengue NS1 antigen persisted in patients with DHF and that it could be possibly used as a marker of severe dengue .…”
Section: Introductionsupporting
confidence: 63%
“…The study done by Paranavitane et al, (2014), found that platelet counts were lower in those who were NS1 antigen positive at the time of admission, but this was not significant. However, interestingly serum NS1 antigen levels significantly correlated with a serum interleukin (IL)-10 levels which are suggested as a possible marker of severe clinical disease.…”
Section: Resultsmentioning
confidence: 90%
“…However, due to the need for advanced laboratory facilities these two methods may not be suitable for routine diagnosis of dengue virus infection early in the disease in resource poor communities (Paranavitane et al, 2014). Serological diagnosis offers many advantages including more flexible schedules for testing, lower cost, and more widely available reagents.…”
Section: Article Infomentioning
confidence: 99%
“…Hence, the positivity to NS1 antigen should alert the treating clinician to closely monitor these children for early detection of the complications. 14,15 Thrombocytopenia was more commonly seen among children who were admitted in intensive care unit in comparison to those in the paediatric wards. Thrombocytopenia is defined as a platelet count below 1,50,000/cumm.…”
Section: Discussionmentioning
confidence: 99%